2023
DOI: 10.1002/app.53889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic vulcanization on the performance of high content rubber modified asphalt

Abstract: High content rubber modified asphalt (HCRA) is usually prepared with devulcanized rubber (DR) in asphalt with good workability. However, the high‐temperature properties of HCRA deteriorate simultaneously. In this study, dynamic vulcanization approach was adopted to improve the high‐temperature properties of HCRA without mitigating the workability and low‐temperature performance of modified binder blends. The dynamic vulcanization process and mechanism were investigated based on the gel content, related chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Rubberized asphalt is widely used in stress-absorbing layers and rutting-resistant sections of asphalt pavements due to its exemplary environmental performance, rutting resistance, and durability, thus prolonging the pavement's service life [10]. For rubberized asphalt, a rubber powder content of over 25% can become a high-content rubberized asphalt, and a large amount of research has proven the feasibility of high-content rubberized asphalt [11,12]. In recent years, it has been found that highcontent rubberized asphalt (HCRA) has better performance in terms of high-temperature rutting resistance and fracture resistance compared to ordinary RA [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Rubberized asphalt is widely used in stress-absorbing layers and rutting-resistant sections of asphalt pavements due to its exemplary environmental performance, rutting resistance, and durability, thus prolonging the pavement's service life [10]. For rubberized asphalt, a rubber powder content of over 25% can become a high-content rubberized asphalt, and a large amount of research has proven the feasibility of high-content rubberized asphalt [11,12]. In recent years, it has been found that highcontent rubberized asphalt (HCRA) has better performance in terms of high-temperature rutting resistance and fracture resistance compared to ordinary RA [13,14].…”
Section: Introductionmentioning
confidence: 99%